2021
DOI: 10.1302/2633-1462.21.bjo-2020-0172.r1
|View full text |Cite
|
Sign up to set email alerts
|

Cementless knee arthroplasty: a review of recent performance

Abstract: Cementless knee arthroplasty has seen a recent resurgence in popularity due to conceptual advantages, including improved osseointegration providing biological fixation, increased surgical efficiency, and reduced systemic complications associated with cement impaction and wear from cement debris. Increasingly younger and higher demand patients are requiring knee arthroplasty, and as such, there is optimism cementless fixation may improve implant survivorship and functional outcomes. Compared to cemented implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…Failure rates are two-fold higher for young patients 17 , who present a 35% revision risk in the 40-year follow-up upon cemented hip arthroplasties 18 . Implant technologies using uncemented fixations are thus significantly increasing worldwide 19 , particularly for younger and active patients whose lifestyle places heavy demands on implants 20 . Cementless fixations aim to maximize implant survival and outperform the mid- and long-term high deterioration risk of cemented implants 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure rates are two-fold higher for young patients 17 , who present a 35% revision risk in the 40-year follow-up upon cemented hip arthroplasties 18 . Implant technologies using uncemented fixations are thus significantly increasing worldwide 19 , particularly for younger and active patients whose lifestyle places heavy demands on implants 20 . Cementless fixations aim to maximize implant survival and outperform the mid- and long-term high deterioration risk of cemented implants 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Cementless fixations aim to maximize implant survival and outperform the mid- and long-term high deterioration risk of cemented implants 21 , 22 . Nevertheless, the risk of bone loss is higher due to stress-shielding using uncemented fixations, given the reduced mechanical stimuli delivered to peri-implant bone structures upon implant insertion 6 , 20 , 21 . Unstable bone–implant fixations triggered by stress-shielding can induce aseptic loosening, an adverse bone remodeling response that exceeds 50% of the revision indications 6 , 9 , 10 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…POD has long been acknowledged as a significant complication in surgery patients. With the aging of the population and the increase of joint diseases, the demand for joint replacement surgery is also increasing [ 16 ]. Studies have shown that the incidence of POD after major surgery is 20% to 50% in people over the age of 60 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“… 5 A recent review evaluating the functional outcomes and implant survivorship with new generations of cementless TKAs has shown encouraging results for this type of fixation in primary TKA. 6 The authors also highlighted the importance of high-quality reporting of functional outcome and implant survivorship in the long term. To our knowledge, there are no other RSA studies with rTKAs, and therefore no data to act as reference when investigating the future effects of these patterns of migration.…”
Section: Introductionmentioning
confidence: 99%